Waliyulloh dan Karamah: Perbedaan dan Persamaanya Pandangan Masyarakat terhadap Waliyullah - Prayogi, Rizky Bintang; Mustofa, Mukhammad Firman; Maulana, Mukhammad Arif Luqniy; Alfurqon, Muhammad Naam; Faisol, Faisol (Maliki Interdisciplinary Journal, 2025)
Waliyullah is a fundamental concept in Islamic teachings which refers to servants of Allah who have a high spiritual closeness to Allah SWT through deep faith and devotion. This research examines the concept of waliyullah based on the basis of the Koran, especially Surah Yunus verses 62-63, as well as the perspective of classical scholars such as Al-Ghazali and Al-Qusyairi. Waliyullah is defined as an individual who always carries out Allah's commands and avoids His prohibitions in everyday life, characterized by ma'rifah (deep knowledge of Allah), mahabbah (sincere love), and prioritizing Allah's pleasure over lust. The saints of Allah do not experience fear and sadness as mentioned in the Qur'an because of their steadfast faith and piety.